Study of Imageability in the Pajak Ikan Lama Medan - Annisa Widhiyanti; Dwi Lindarto Hadinugroho; Wahyu Utami (International Journal of Architecture and Urbanism, 2024)
The Pajak Ikan Lama area is one of the old town commercial areas in Medan City that has a row of Chinatown shophouse buildings with various local trading activities. The rapid economic growth and modernization in this area is feared to have an impact on the physical aspects and spatial quality of the area that does not show its concept and aesthetics as an old town commercial area. The irregularity of activities that occur in this area also affects the condition of visitors in observing and understanding this area. These problems affect the imageability of the Pajak Ikan Lama area. The purpose of this research is to examine the formation of imageability of the Pajak Ikan Lama area based on its supporting qualities, such as legibility, enclosure, human scale, complexity, coherence, linkage, and transparency. The method used in this research is descriptive qualitative with case study research type. The results of this research are expected to reveal the formation of imageability of the Pajak Ikan Lama area based on its supporting qualities.